Ferroptosis-related gene signature predicts the clinical outcome in pediatric acute myeloid leukemia patients and refines the 2017 ELN classification system - Tao, Yu; Wei, Li; You, Hua (Frontiers in Molecular Biosciences, 2022)
Background: The prognostic roles of ferroptosis-related mRNAs (FG) and lncRNAs (FL) in pediatric acute myeloid leukemia (P-AML) patients remain unclear. Methods: RNA-seq and clinical data of P-AML patients were downloaded from TARGET project. Cox and LASSO regression analyses were performed to identify FG, FL, and FGL (combination of FG and FL) prognostic models, and their performances were compared. Tumor microenvironment, functional enrichment, mutation landscape, and anticancer drug sensitivity were analyzed. Results: FGL model of 22 ferroptosis-related signatures was identified as an independent parameter and its performance showed better than FG, FL, and 4 additional public prognostic models. FGL model divided patients in discovery cohort (N=145), validation cohort (N=111), combination cohort (N=256), and intermediate-risk group (N=103) defined by the 2017 European Leukemia Net (ELN) classification system into two groups with distinct survival. The high-risk group was enriched in apoptosis, hypoxia, TNFA signaling via NFKB, reactive oxygen species pathway, oxidative phosphorylation, and p53 pathway and associated with low immunity, while patients in the low-risk group may benefit from anti-TIM3 antibodies. In addition, patients within FGL high-risk group might benefit from treatment using SB505124_1194 and JAK_8517_1739. Conclusions: Our established FGL model may refine and provide a reference for clinical prognosis judgment and immunotherapies for P-AML patients.